Gender differences in the kinematics of unanticipated cutting in young athletes - Ford, K. R.; Myer, G. D.; Toms, H. E.; Hewett, T. E. (Medicine & Science in Sports & Exercise, 2005)
Purpose: Anterior cruciate ligament (ACL) injuries occur at a greater rate in adolescent females compared with males who participate in the same pivoting and jumping sports. The purpose of this study was to compare knee and ankle joint angles between males and females during an unanticipated cutting maneuver. The hypotheses were that female athletes would display increased knee abduction, increased ankle eversion and decreased knee flexion during the unanticipated cutting maneuver compared with males.